The effect of the menstrual cycle and oral contraceptives on acute responses and chronic adaptations to resistance training: A systematic review of the literature - Thompson, B.; Almarjawi, A.; Sculley, D.; Janse de Jonge, X. (Sports Medicine, 2020)
Background: Resistance training is well known to increase strength and lean body mass, and plays a key role in many female athletic and recreational training programs. Most females train throughout their reproductive years when they are exposed to continuously changing female steroid hormone profiles due to the menstrual cycle or contraceptive use. Therefore, it is important to focus on how female hormones may affect resistance training responses. Objective: The aim of this systematic review is to identify and critically appraise current studies on the effect of the menstrual cycle and oral contraceptives on responses to resistance training. Methods: The electronic databases Embase, PubMed, SPORTDiscus and Web of Science were searched using a comprehensive list of relevant terms. Studies that investigated the effect of the menstrual cycle phase or oral contraceptive cycle on resistance training responses were included. Studies were also included if they compared resistance training responses between the natural menstrual cycle and oral contraceptive use, or if resistance training was adapted to the menstrual cycle phase or oral contraceptive phase. Studies were critically appraised with the McMasters Universities Critical Review Form for Quantitative Studies and relevant data were extracted. Results: Of 2007 articles found, 17 studies met the criteria and were included in this systematic review. The 17 included studies had a total of 418 participants with an age range of 18-38 years. One of the 17 studies found no significant differences in acute responses to a resistance training session over the natural menstrual cycle, while four studies did find changes. When assessing the differences in acute responses between the oral contraceptive and menstrual cycle groups, two studies reported oral contraceptives to have a positive influence, whilst four studies reported that oral contraceptive users had a delayed recovery, higher levels of markers of muscle damage, or both. For the responses to a resistance training program, three studies reported follicular phase-based training to be superior to luteal phase-based training or regular training, while one study reported no differences. In addition, one study reported no differences in strength development between oral contraceptive and menstrual cycle groups. One further study reported a greater increase in type I muscle fibre area and a trend toward a greater increase in muscle mass within low-androgenic oral contraceptive users compared with participants not taking hormonal contraceptives. Finally, one study investigated androgenicity of oral contraceptives and showed greater strength developments with high androgenic compared with anti-androgenic oral contraceptive use. Conclusions: The reviewed articles reported conflicting findings, and were often limited by small participant numbers and methodological issues, but do appear to suggest female hormones may affect resistance training responses. The findings of this review highlight the need for further experimental studies on the effects of the menstrual cycle and oral contraceptives on acute and chronic responses to resistance training. Key Points: The effects of both the menstrual cycle and oral contraceptive use on acute responses to resistance training remain unclear. Follicular phase-based resistance training programs appear to result in better responses than luteal phase-based and regular training programs. Further research is needed in this area, including a focus on different types of oral contraceptives.